2007
DOI: 10.1097/fpc.0b013e3282f06646
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mutations in the BCHE gene in patients with prolonged duration of action of mivacurium or succinylcholine during anaesthesia

Abstract: Two novel variants of BCHE are silencing the enzyme function. BCHE*FS126 results in a truncated protein lacking the active site and is therefore inactive. The second variant is BCHE*328D, also resulting in an inactive protein, as this change in amino acid is radical and furthermore situated in the gorge harbouring the active site. These variants result in extensively prolonged duration of action of succinylcholine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…nAChRs are considered to be a strong antagonist on succinylcholine (suxamethonium), they are used for recovery from near fatal hyperthermia [43] and neuromuscular junction paralysis in anesthesia [44]. Since succinylcholine is converted by plasmatic butyrylcholinesterase, butyrylcholinesterase dysfunctional patients are extremely sensitive to succinylcholine and recovery from its application lasts longer when compared to individuals with fully active butyrylcholinesterase [45]. …”
Section: Acetylcholine Receptorsmentioning
confidence: 99%
“…nAChRs are considered to be a strong antagonist on succinylcholine (suxamethonium), they are used for recovery from near fatal hyperthermia [43] and neuromuscular junction paralysis in anesthesia [44]. Since succinylcholine is converted by plasmatic butyrylcholinesterase, butyrylcholinesterase dysfunctional patients are extremely sensitive to succinylcholine and recovery from its application lasts longer when compared to individuals with fully active butyrylcholinesterase [45]. …”
Section: Acetylcholine Receptorsmentioning
confidence: 99%
“…These findings combined with those indicating that exposure to stress can inhibit tonic pain and that intra-VTA morphine induces analgesia in the formalin test suggest that the endogenous release of opioids in the VTA might be a mechanism underlying the stress-induced inhibition of tonic pain. This has been supported by the finding that intra-VTA infusions of the opioid receptor antagonist, naltrexone, block stress-induced analgesia in the formalin test [3]. In addition, it has been proposed that release of the tachykinin neuropeptide, substance P (SP), in the VTA might play a similar role in the stress-induced suppression of tonic pain.…”
Section: Dopamine and Painmentioning
confidence: 97%
“…Clinical observations of such inherited differences in drug effects were first documented in the 1950s, exemplified by the prolonged muscle relaxation after the drug became known as suxamethonium (an inhibitor of the breakdown of acetylcholine) and by an inherited deficiency in the genes that encode the enzyme responsible for the breakdown of this drug as marked by plasma cholinesterase (the enzyme which breaks down acetylcholine) [3]. The second gene-based drug response was observed when researchers found that certain patients bled to death after they were treated with an anti-malarial therapy, because they carried a gene variant that lowered their blood cell glucose 6-phosphate dehydrogenase activity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Na temelju različite aktivnosti prema supstratima, kao i različite inhibicije sa specifi čnim inhibitorima, moguće je odrediti neke genotipove butirilkolinesteraze; UU, UA, AA/AS i FF/FS (38,39). Međutim, ostale inačice tihe i fl uoridne BChE, kvantitativne inačice i rijetke inačice moguće je odrediti genotipiziranjem (40). Kvantitativne inačice: K-, J-i Hammersmithova inačica imaju sniženu koncentraciju BChE u serumu i prisutne su u 30 %, 70 % odnosno 90 % nižoj koncentraciji od uobičajene BChE.…”
Section: Inačice Bcheunclassified
“…Klinički je najzanimljivija atipična inačica koja mišićni relaksans sukcinildikolin hidrolizira vrlo sporo, a nosioci takve inačice rizične su osobe u slučaju primjene sukcinildikolina jer u vrijeme anestezije mogu doživjeti produženi respiratorni arest. Valja napomenuti da osobe koje su nosioci tihe inačice BChE ili neke od kvantitativnih inačica sa sniženom koncentracijom BChE nemaju nikakvih zdravstvenih teškoća, ali čine rizičnu skupinu kod trovanja pesticidima i u slučaju primjene lijekova za Alzheimerovu bolest (donepezil i huperzin A) (12,40). Grupiranjem svih tihih i fl uoridnih inačica u dvije skupine, a izuzimanjem H, J, Cynthiane i drugih rijetkih inačica može se govoriti o 15 mogućih genotipova ljudske BChE (12).…”
Section: Inačice Bcheunclassified